2002
DOI: 10.1074/jbc.m204309200
|View full text |Cite
|
Sign up to set email alerts
|

Glia- and Neuron-specific Expression of the Renin-Angiotensin System in Brain Alters Blood Pressure, Water Intake, and Salt Preference

Abstract: The purpose of this study is to examine the regulation of blood pressure and fluid and electrolyte homeostasis in mice overexpressing angiotensin II (Ang-II) in the brain and to determine whether there are significant physiologic differences in Ang-II production in neurons or glia. Therefore, we generated and characterized transgenic mice overexpressing human renin (hREN) under the control of the glial fibrillary acidic protein (GFAP) promoter (GFAP-hREN) and synapsin-I promoter (SYN-hREN) and bred them with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
124
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 107 publications
(129 citation statements)
references
References 41 publications
4
124
1
Order By: Relevance
“…Consistent with this are reports that ANG II exists in nerve terminals and glial cell populations (8,21). We previously demonstrated that ANG II produced by either neurons or glial cells is functionally active (28). This was accomplished by generating transgenic mice expressing both human AGT (hAGT) and/or human renin (hREN) driven by either the synapsin-I (SYN) promoter, a neuronal promoter, or the glial fibrillary acidic protein (GFAP) promoter, a glial promoter (27)(28)(29).…”
supporting
confidence: 72%
See 4 more Smart Citations
“…Consistent with this are reports that ANG II exists in nerve terminals and glial cell populations (8,21). We previously demonstrated that ANG II produced by either neurons or glial cells is functionally active (28). This was accomplished by generating transgenic mice expressing both human AGT (hAGT) and/or human renin (hREN) driven by either the synapsin-I (SYN) promoter, a neuronal promoter, or the glial fibrillary acidic protein (GFAP) promoter, a glial promoter (27)(28)(29).…”
supporting
confidence: 72%
“…The tissue specificity and cell specificity of expression in those models was previously reported (28,29). To obtain concurrent measurements, we first compared resting BP in G-AII, N-AII, and control mice.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations